2016
DOI: 10.1002/jsfa.7541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave pretreatment and transglutaminase crosslinking on the gelation properties of soybean protein isolate and wheat gluten mixtures

Abstract: The effect of microwave pretreatment is useful in advancing gelation characters of MTGase-induced SPI/WG gels and provides the possibility for expanding the application of food protein. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 52 publications
5
27
0
Order By: Relevance
“…Moreover, the exposure of sulfhydryl and hydrophobic groups which resulted from microwave treatments promoted hydrophobic interactions and disulfide bond formation to generate denser and compact gel cross‐linking when being induced by laccase. These result stood in line with Qin et al where SPI‐wheat gluten gels formed by transglutaminase also showed denser microstructure after microwave treatments (Qin et al, ; Wang et al, ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the exposure of sulfhydryl and hydrophobic groups which resulted from microwave treatments promoted hydrophobic interactions and disulfide bond formation to generate denser and compact gel cross‐linking when being induced by laccase. These result stood in line with Qin et al where SPI‐wheat gluten gels formed by transglutaminase also showed denser microstructure after microwave treatments (Qin et al, ; Wang et al, ).…”
Section: Resultssupporting
confidence: 86%
“…The microstructure of control sample and samples treated by microwave were investigated by SEM. As shown in Figure 5 wheat gluten gels formed by transglutaminase also showed denser microstructure after microwave treatments (Qin et al, 2016b;Wang et al, 2017). Our results demonstrated that microwave pretreatment provides a significant improvement in the formation of disulfide bonds and hydrophobic interactions, decreasing free SH group content, which resulted in a homogeneous network forming.…”
Section: Microstructural Characterization By Sem Analysissupporting
confidence: 52%
“…used dilute H 2 SO 4 solution to treat ground soybean meal held in a water bath at 80 °C for 2 h. Acid pretreatment helps to hydrolyze hemicellulose, reducing cellulose crystallinity and increasing the surface area and pore volume to increase the yield. Similarly, Qin et al . and Wang et al .…”
Section: Protein Extractionmentioning
confidence: 68%
“…Zhang et al 47 used dilute H 2 SO 4 solution to treat ground soybean meal held in a water bath at 80 ∘ C for 2 h. Acid pretreatment helps to hydrolyze hemicellulose, reducing cellulose crystallinity and increasing the surface area and pore volume to increase the yield. Similarly, Qin et al 48 and Wang et al 49 used microwave to aid in disruption of the tissue to increase the protein yield. Li et al 50 used ultrasound in addition to microwave and studied the structural properties of SPIs.…”
Section: Protein Extractionmentioning
confidence: 99%
“…In addition, Da Rós, Freitas, Perez and de Castro14 reported the application of lipase/MI treatment to accelerate the enzymatic synthesis of biodiesel, and high catalytic efficiency ( K cat / K m ) values have also been achieved in the microwave-assisted digestion of β-LG by pronase15. Finally, MI can be used in the MTGase catalysis of covalent cross-linking, and to improve the gel strength of soybean protein isolate gels16.…”
mentioning
confidence: 99%